2019
DOI: 10.1177/2158244019854652
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Statistical Process Control Methods to Monitor Interview Duration During Survey Data Collection

Abstract: Despite general agreement regarding the usefulness of statistical process control (SPC) tools for monitoring paradata, using SPC from an early phase of the survey fieldwork is rather rare. This study focuses on one type of paradata-interview duration-to fill this void. First, we establish a procedure based on the idea of enabling fieldwork monitoring for the seventh round of the European Social Survey in Belgium from its start. The impact of respondent characteristics on interview duration is controlled for by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, care should be taken when including indicators that are expected and "allowed" to vary across respondents (or interviewers) or across time (e.g., interview duration). We would suggest that before being used to identify outliers, the impact of influencing factors on these indicators should be controlled for using multiple regression models (Jin et al 2019), multilevel models (Couper and Kreuter 2012), or penalized spline models (Schafer 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, care should be taken when including indicators that are expected and "allowed" to vary across respondents (or interviewers) or across time (e.g., interview duration). We would suggest that before being used to identify outliers, the impact of influencing factors on these indicators should be controlled for using multiple regression models (Jin et al 2019), multilevel models (Couper and Kreuter 2012), or penalized spline models (Schafer 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…• Demonstration of the usefulness of SPC for monitoring paradata for assessing the quality of data obtained in surveys (Jin, Vandenplas & Loosveldt, 2019).…”
Section: Spc Applicationsmentioning
confidence: 99%
“…Out of its available tools, the control chart is the most important and most widely used. Although initially applied in industrial fields, the control chart has found uses in many non-industrial fields, such as public health (see the review article by Thor et al 2007), finance (e.g., Kovářık and Sarga 2014;Bodnar and Schmid 2011;Bilson et al 2010), and even surveys (Jin and Loosveldt 2020;Jin et al 2019;Sirkis et al 2011). It calculates control limits using statistical equations, and graphically presents the fluctuations of the quality characteristic of a process.…”
Section: Introductionmentioning
confidence: 99%